ESTIMATION METHODOLOGY OF HEATING THE CONTACT PLACE OF CONTACT WIRE WITH CONTACT STRIP OF PANTOGRAPH - Mukha, А. М.; Ustymenko, D. V. (Science and Transport Progress, 2020)
Purpose. The main purpose of our work is to develop a method for assessing the heating temperature of the contact area of contact wire with contact strip of pantograph (the contact wire element – the contact strip element of pantograph, in abbreviated form – CWE – CSEP) for parking conditions when preparing the train for the trip with the determination of the maximum current load on given node. Methodology. We proposed to consider the CWE – CSEP contact from the point of view of the classical theory of electrical contact and heating of a homogeneous body. Findings. The features of thermal state of the current collection unit of CWE – CSEP in the conditions of preparing the electric rolling stock for the trip are considered. Within the framework of the study a methodology for assessing the heating temperature of the zone of power sliding contact in the conditions of train preparation for the trip has been developed. The application of the methodology will help reduce the number of burnings through of the contact wire due to the precise choice of the heating/conditioning time of the train for a certain heating/conditioning current when preparing the electric rolling stock for the trip. Originality. It has been established that the reason for burnings through the contact wire in stalls when preparing the train for the trip is the excess of permissible temperature of the power sliding contact as a result of prolonged action of the heating/conditioning current. In contrast to the standard approach for determining the duration of the train heating, the proposed methodology takes into account additional factors, namely, the wear and condition of the contact wire, condition of contact strip of the pantograph. This methodology is based on the classical theory of electrical contact and the theory of heating a homogeneous body, which allows accurate assessment of the thermal state of a power sliding contact, and is convenient enough for use in operating conditions. Practical value. The results of the work are of practical value, since the technology of preparing a train for a trip can be supplemented by calculating the temperature of the CWE – CSEP contact in accordance with the proposed methodology. This will allow applying a set of measures to prevent burnings through of the contact wire in case of possible temperature exceeding the permissible value for a specific train in specific conditions.